Polemik Surat Pemusik (Studi Penamaan Surat dalam Al-Qur'an) - Oscar Wardhana Windro Saputro; Muhammad Raflie Al-Fath (STAI Ali bin Abi Thalib Surabaya, 2025)
This study aims to explore the process of naming and classifying surahs in the Qur'an that has been done by scholars in the branch of ‘ulu>m Al-Qur’an. It will also examine the naming and translation of Surah Ash-Shu'ara into a musician's Surah and its implications based on the rules of translation and tafsir. This research uses a qualitative approach with the type of library research. The data sources of this research are books in the field of ‘ulu>m Al-Qur’an and books of tafsir. The Muslim community in Indonesia has understood that the Qur'an consists of 114 letters, each of which has a special name and its meaning from the translation of the Al-Qur'an Mushaf. Until in 2024 there was a discussion about the name of a letter in the Qur'an that was translated differently from what was written in the translation of the Qur'an in general. This happened when Surah al-Syu'ara in the translation of the Mushaf was translated as the poets, then translated as the letter of the musicians. Suddenly, this provoked an uproar in the community, especially in the digital era where news circulates quickly (viral). The result of this study is that the naming of letters in the Qur'an is divided into two, namely tawqi>fy and ijtiha>dy. There are three main patterns of naming surahs in the Qur'an, namely based on the Prophet's orders, the ijtihad of the Companions and based on the beginning of the verse. The translation of Surah Ash-Shu'ara into Surah of Musicians does not fulfill the rules of translation or tafsir because poetry and music are two different things in essence and in the meaning of translation in the dictionary, neither textually nor contextually can be equated. The translation of the word Ash-Shu'ara as musicians will damage the meaning of the verses in the Qur'an and can be categorized as tahri>f and includes tafsir bi al-ra'y al-madhmu>m or interpretation by reasoning that is denounced.